Legal Protection for Borrowers and Business Dispute Resolution in Fintech Lending Services - Lu Sudirman; Hari Sutra Disemadi (Jurnal Jurisprudence, 2021)
Objective: This study aims to identify how progressive the legal protection for borrowers as a fintech lending service user is and how the business dispute resolution model for these services is applied in Indonesia.Methodology: This research utilized a normative juridical research method with legal and conceptual approaches. The data used in this research were secondary legal data analyzed using qualitative analysis techniques to draw the right conclusions.Findings: Fintech lending service is an alternative solution for the community to carry out the procedure of fund borrowing by accessing the sites and applications of lending companies without having to go through banking transactions and financing institutions. Although fintech lending contributes to various financial activities, this innovation encounters issues in protecting consumers as borrowers. The rise of personal data misuse, intimidating money collection procedures, and sexual harassment have threatened consumers' sense of security, so law enforcement is urgently needed to overcome these crimes. Regarding the borrower protection in the fintech business, OJK, under its power, has ratified “OJK Regulation Number 77/POJK.07/2016 concerning Information Technology-Based Fund Borrowing Services”. However, these regulations cannot protect borrowers, so the problems continue to rise. Furthermore, business disputes that arise in fintech lending need further guidance from independent institutions and the government to protect consumers and business actors when involved in disputes. Applying a non-litigation route, namely Alternative Dispute Resolution (ADR), is recommended with the disputing parties and third parties.Implication: This research is expected to support literacy to the public in selecting the right online financing and loan institutions. In addition, the results of these studies can be a source of reference for legal scholars.Novelty/Originality: In contrast to previous research, this research focuses on studying how important the legal protection of borrowers who use fintech services is and the steps that can be taken to resolve business disputes in the industry that have not yet been specifically identified.